Tiger Crisis: a (MIS)understood Development Paradigm - Gupta, A. K.; Srivastava, Rajeev K. (Indian Forester, 2005)
Tiger crisis is a stark reality of our times. There is deep concern about but its implications are not fully and properly recognized. Conserving the tiger is to conserve the biodiversity and consequently nature itself, so very essential for our own existence. Development poses a great problem as it is diametrically opposed to conservation, in essence craze for tangible benefits vis-it-vis intangible benefits goes against objectives of conservation. Development of scheduled tribes living in and around forests, upto developed nation standards will further tax our limited resources to the detriment of Homo sapiens. The authors suggest levying a tax on hotel industry, earning from eco-tourism, to provide funds for the welfare of ecosystem people. Stringent measures should be taken to curb poaching, illicit trade in wildlife and its production, revamp the monitoring system by inducting scientifically trained person in the forest services etc. and bring back the lost glory.